Maturation and Post-Harvest Resting of Fruits Affect the Macronutrients and Protein Content in Sweet Pepper Seeds - Colombari, Lidiane Fernandes [UNESP]; Chamma, Larissa [UNESP]; da Silva, Gustavo Ferreira [UNESP]; Zanetti, Willian Aparecido Leoti [UNESP]; Putti, Fernando Ferrari [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP] (MDPI, 2022)
There are few studies about the influence of fruit maturation and post-harvest resting on seed composition, which can be necessary for seedling development and future establishment. Thus, the objective of this study was to evaluate the effect of maturation and post-harvest resting of fruits on the macronutrient and protein content of sweet pepper seeds. The experimental design was a randomized block, with eight treatments, in a 4 × 2 factorial arrangement. The first factor was fruit maturation stages (35, 50, 65 and 80 days after anthesis), and the second, with and without post-harvest resting of the fruits for 7 days. The characteristics evaluated in seeds were the dry weight of one thousand seeds, macronutrient content, and content of albumin, globulin, prolamin and glutelin proteins. There were reductions in K, Ca and Mg content, and an increase in seed content of albumin, globulin and prolamins as a function of the fruit maturation stage. Post-harvest resting of the fruits provided higher Ca content and protein albumin in seeds. The decreasing order of macronutrients and protein content in seeds, independent of fruit maturation and resting stage of the fruits, was N > K > P > Mg > S > Ca, and albumin > globulin ≈ glutelin > prolamine, respectively.
Keywords: Capsicum annuumL; maturation; nutritional quality; seed chemical composition